Conflict and control in the contemporary workplace: Structured antagonism revisited. Issue 3 (27th April 2022) - Edwards, Paul; Hodder, Andy
Abstract: The concept of a structured antagonism lying at the heart of the employment relationship is widely cited but also commonly misinterpreted. The paper firstly returns to the origin of the concept to locate its approach to workplace industrial relations. It forms part of labour process analysis, within which its distinct emphasis is two‐fold: a focus on levels of analysis, such that the connections between the underlying antagonism and concrete behaviour can be interrogated; and a preference for comparative analysis, which allows the relevant processes to be identified. In this paper, we apply these themes to contemporary workplaces such as those in the gig economy. Recent research demonstrates substantial empirical and theoretical progress but can be taken further using the above two ideas. A methodological checklist emerges to guide a future programme of research.